Problems of multi-criteria synthesis of complex technical systems and methods of their solution - Ziatdinov, Yu.K.; Klymova, A.S.; Polukhin, A.V. (Problems of Informatization and Management, 2023)
The article examines the main problematic issues and methods of solving the problem of multi-criteria parametric synthesis of complex technical systems during scientific and technical research at the initial stages of their development. As complex technical systems, systems related to rocket and space technology are considered. The development of complex aviation systems today, in the conditions of the limitation of financial and production resources, necessitates the in-depth study of a number of scientific and technical problems, which largely depend on the tactical and technical characteristics of the system and the success of its application. The selection of tactical and technical characteristics of the system and their further optimization is the task of multi-criteria parametric synthesis. The article deals with the general formulation of the multi-criteria optimization problem, justification and recommendations regarding the most preferable option for building a complex system. The following problematic issues of vector optimization are considered: normalization of criteria; taking into account the priority of criteria; highlighting the area of compromises; choosing a scheme of compromises and a single solution. In addition, another problem when solving vector optimization problems is the choice of instrumental and methodical means for conducting scientific and applied research, engineering works. In order to solve these problematic issues, the article considers special methods and algorithms of multi-criteria parametric synthesis and mathematical modeling regarding the selection of the optimal system construction option. These methods make it possible to evaluate alternative options for building a system, justify and give recommendations regarding the most preferable option. Currently, there are a large number of methods and software products that provide wide opportunities for solving the problem of vector optimization and conducting various types of data analysis. For example, the most acceptable and effective are SPSS, PS PRIAM, STATISTICA, ProSto, as well as the use of a large number of existing and newly created modules based on the integrated Microsoft Office package.